Principal's Leadership in Improving Teacher Discipline - Out Chanthea (Universitas Negeri Malang, 2014)
The purpose of this study is to understand  Principal's Leadership in Improving Teacher Discipline and it is investigated under the focus: (1) factors needed by principals to influence teacher discipline effectively, (2) techniques are used by headmaster to improve teacher discipline, (3) the process of teacher motivation in improving the discipline, (4) the reward and punishment systems applied by the principal to improving teacher discipline, and (5) the process of monitoring the implementation of teacher discipline. This research used a qualitative approach with a case-study design. Data collection techniques which were applied are: (1) in-depth interview, (2) ob-servation, and (3) documentation. The results of this study are presented as followings. (1) Factors needed by principal to influence teacher discipline effectively are: a) education background, b) work experience, c) a positive model, d) awareness of the role and responsibility as a school leader, e) professional character. (2) Techniques used by headmaster to apply teacher discipline are: a) reminding, b) discussion, c) meeting, d) evaluation, e) communication f) the letter, and g) the reward and punish-ment. (3) The process of teacher motivation in improving the discipline are: a) good involvement and communication,  b) training programs, c) accepting suggestions/discussion, d)  the outbound activity, e) getting involved with all school activities, f) celebrating all  special holiday, both national and religious holidays, g)  staff promotion, and i) the bonus salary. (4) the reward and punishment sys-tems applied by the principal to improvee teacher discipline are:  a) appraisals,  b) a prize and  a cer-tificate of appreciation,  c) bonus salary,  d) discussion about the problem, warning letters, and dismissing letter, and e) salary suspension and salary decreases. (5) The process of monitoring the implementation of teacher discipline are: a) management system/organizing structure, and b) direct and indirect supervision. Key Words: principal's leadership, teacher discipline, elementary school